Numerical simulation and mechanism research of flow-induced vibration of porous airfoils - Ying, Changjie; Guan, Guan; Liang, Guopeng (Physics of fluids (1994), 2025)
The porous airfoil, inspired by avian wing morphology, exhibits complex flow-induced vibrations (FIVs) that significantly impact aerodynamic performance. This study employs computational fluid dynamics (CFD) methods to investigate FIV mechanisms of the porous airfoil through parametric analyses of aspect ratio (AR), thickness ratio (TR), and additional sinusoidal motion in the wing. A high-fidelity CFD model is developed and validated against wind tunnel data, achieving errors within 10%. Key findings reveal: (1) non-monotonic lift variation with AR, peaking at AR=6 due to suppressed vortex shedding; (2) linear reduction in lift coefficient with increasing TR, attributed to diminished pressure gradients; (3) periodic lift oscillations synchronized with sinusoidal motion, where shorter periods (0.1 s) induce stronger aerodynamic damping. The derived mechanisms provide guidelines for optimizing bio-inspired porous airfoils in applications requiring vibration suppression or energy harvesting.